2017
DOI: 10.1111/jcal.12215
|View full text |Cite
|
Sign up to set email alerts
|

The effects of computer simulation and animation (CSA) on students' cognitive processes: A comparative case study in an undergraduate engineering course

Abstract: This study focuses on the investigation of the effects of computer simulation and animation (CSA) on students' cognitive processes in an undergraduate engineering course. The revised Bloom's taxonomy, which consists of six categories in the cognitive process domain, was employed in this study. Five of the six categories were investigated, including remember, understand, apply, analyze, and evaluate. Data were collected via a think‐aloud protocol involving two groups of student participants: One group learned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Studies that reported the results of an empirical study involving undergraduates as participants using a V-Lab in either 2D or 3D format as part of laboratory learning and were published between January 2008 and December 2018 were included and those that did not meet this criterion were excluded (e.g., Schott and Marshall 2018;Uribe et al 2016). Manuscripts that did not include the collection and analysis of data on student outcomes (e.g., learning, perception, self-efficacy, motivation) were excluded (e.g., Dalgarno et al 2009;Fang and Tajvidi 2018;Kang et al 2018;Williams 2010). Additionally, Achuthan et al (2017); Reyes-Aviles and Aviles-Cruz (2018); and Tetour et al (2011) were excluded because these studies focused on remote experiments and/or augmented reality environments.…”
Section: Inclusion-exclusion Criteriamentioning
confidence: 99%
“…Studies that reported the results of an empirical study involving undergraduates as participants using a V-Lab in either 2D or 3D format as part of laboratory learning and were published between January 2008 and December 2018 were included and those that did not meet this criterion were excluded (e.g., Schott and Marshall 2018;Uribe et al 2016). Manuscripts that did not include the collection and analysis of data on student outcomes (e.g., learning, perception, self-efficacy, motivation) were excluded (e.g., Dalgarno et al 2009;Fang and Tajvidi 2018;Kang et al 2018;Williams 2010). Additionally, Achuthan et al (2017); Reyes-Aviles and Aviles-Cruz (2018); and Tetour et al (2011) were excluded because these studies focused on remote experiments and/or augmented reality environments.…”
Section: Inclusion-exclusion Criteriamentioning
confidence: 99%
“…This virtual basic application-based learning media can increase students' interest and activities in the learning process so that learning in the classroom is more fun and more meaningful. One of the studies conducted by (Fang & Tajvidi, 2018) explains that students who learn by utilizing computer-based technology can significantly increase student activity, in line with Bloom (Fang & Tajvidi, 2018)…”
Section: Development Stagementioning
confidence: 81%
“…Bloom's Taxonomy of Cognitive Process Domain is used in Higher Education (21,22) . It is an instrument to develop learning objectives, to direct the teaching and learning process, and to assess whether or not the desired mental action has been demonstrated by students (23) , as it favors a hierarchical organization according to levels of complexity and desired and planned cognitive development goals (24) .…”
Section: Bloom's Taxonomy: Cognitive Process Domainmentioning
confidence: 99%